Stress Analysis and Safety Factors of Hand-rail Hoppers Based on the FEA Method - Rinto Hindroyuwono; Rachmat Anggi Marvianto; Siti Sarah Anjani; Muhammad Bintang Pamungkas; Yunus Bakhtiar Arafat (International Journal of Engineering Continuity, 2024)
Ensuring handrails structural integrity and safety in industrial hopper systems is crucial for worker protection and operational efficiency. This study investigates handrail systems design, stress analysis, and safety factors using Finite Element Analysis (FEA) via SolidWorks. Observations of existing systems revealed deficiencies such as improper welding techniques and unstable mounting, which were addressed through an improved modular handrail design that incorporated standardized dimensions, full-welded joints, and clamped baseplates. The methodology included a comprehensive simulation of the static loads, stress distributions, and deformation patterns validated through physical load testing. Results demonstrated significant improvements, with a reduction in the maximum stress by 25% and deformation by 40%, yielding a safety factor of 1.85. The findings confirm compliance with the industrial safety standards and highlight the robustness of the proposed design. This research contributes to advancing workplace safety through a replicable framework that combines simulation and empirical validation, offering broader applicability to safety-critical industrial components.